Mitochondrial metabolism contributes to oxidative stress and reveals therapeutic targets in chronic lymphocytic leukemia - Jitschin, Regina; Hofmann, Andreas D.; Bruns, Heiko; Gießl, Andreas; Bricks, Juliane; Berger, Jana; Saul, Domenica; Eckart, Michael J.; Mackensen, Andreas; Mougiakakos, Dimitrios (Blood, 2014)
Alterations of cellular metabolism represent a hallmark of cancer. Numerous metabolic changes are required for malignant transformation, and they render malignant cells more prone to disturbances in the metabolic framework. Despite the high incidence of chronic lymphocytic leukemia (CLL), metabolism of CLL cells remains a relatively unexplored area. The examined untreated CLL patients displayed a metabolic condition known as oxidative stress, which was linked to alterations in their lymphoid compartment. Our studies identified mitochondrial metabolism as the key source for abundant reactive oxygen species (ROS). Unlike in other malignant cells, we found increased oxidative phosphorylation in CLL cells but not increased aerobic glycolysis. Furthermore, CLL cells adapted to intrinsic oxidative stress by upregulating the stress-responsive heme-oxygenase-1 (HO-1). Our data implicate that HO-1 was, beyond its function as an antioxidant, involved in promoting mitochondrial biogenesis. Thus ROS, adaptation to ROS, and mitochondrial biogenesis appear to form a self-amplifying feedback loop in CLL cells. Taking advantage of the altered metabolic profile, we were able to selectively target CLL cells by PK11195. This benzodiazepine derivate blocks the mitochondrial F1F0-ATPase, leads to a surplus production of mitochondrial superoxide, and thereby induces cell death in CLL cells. Taken together, our findings depict how bioenergetics and redox characteristics could be therapeutically exploited in CL
EVALuna2:25687